The atypical structure and function of newborn arterial endothelium is mediated by Rho/Rho kinase signaling - Flavahan, Sheila (American Physiological Society, 2014)
Endothelium of fetal or newborn arteries is atypical, displaying actin stress fibers and reduced nitric oxide (NO)-mediated dilatation. This study tested the hypothesis that Rho/Rho kinase signaling, which promotes endothelial stress fibers and inhibits endothelial dilatation, contributed to this phenotype. Carotid arteries were isolated from newborn [postnatal day 1 (P1)], P7, and P21 mice. Endothelial dilatation to acetylcholine (pressure myograph) was minimal at P1, increased at P7, and further increased at P21. Inhibition of Rho (C3 transferase) or Rho kinase (Y27632, fasudil) significantly increased dilatation to acetylcholine in P1 arteries but had no effect in P7 or P21 arteries. After inhibition of NO synthase (N(G)-nitro-l-arginine methyl ester), Rho kinase inhibition no longer increased acetylcholine responses in P1 arteries. Rho kinase inhibition did not affect dilatation to the NO donor DEA-NONOate. The endothelial actin cytoskeleton was labeled with phalloidin and visualized by laser-scanning microscopy. In P1 arteries, the endothelium had prominent transcytoplasmic stress fibers, whereas in P7 and P21 arteries, the actin fibers had a significantly reduced intensity and were restricted to cell borders. Phosphorylation of myosin light chains, a Rho kinase substrate, was highest in P1 endothelium and significantly reduced in P7 and P21 endothelium (laser-scanning microscopy). In P1 arteries, inhibition of Rho (C3 transferase) or Rho kinase (Y27632) significantly reduced the intensity of actin fibers, which were restricted to cell borders. Similarly, in P1 arteries, Rho inhibition significantly reduced endothelial levels of phosphorylated myosin light chains. These results indicate that the atypical function and morphology of newborn endothelium is mediated by Rho/Rho kinase signaling.